Analysis of aging effects on chemical property of human hair by Fourier transform infrared spectroscopy. Issue 1 (24th June 2012) - Kim, Kyung Sook; Park, Hun‐Kuk
<x xml:space="preserve">Abstract</x> Background In the previous work, we investigated the aging effect on morphology and mechanical property of the hair by using atomic force microscopy. Objectives The effects of aging on chemical properties of human hair were investigated by Fourier transform infrared (FT‐IR) spectroscopy. Methods Healthy hair samples with no diseases were collected from 60 Koreans (30 males and 30 females) and they were grouped by age: 1–10, 11–20, 21–30, 31–40, 41–50, and 51–60 years. Results The characteristic parameters of FT‐IR absorbance bands including center frequency, half width, height, and area were analyzed using the Gaussian model. To quantitatively analyze the chemical composition of hair, the height and area of all bands in the spectra were normalized to the amide I centered at 1652–1659 and 1654–1658 cm−1, for male and female hairs, respectively. In all male and female hairs, the spectra of specific components of the hair keratin showed to have the same dependence on aging. The center positions of the bands arising from amide A, CH 3 mode, and amide I were altered by aging. The female hair contains more cystein than the male hair. Changes in the amount of amide II and amide A by aging were more significant in male hair than in female hair. Conclusions The changes in chemical components of the hair according to the ages were shown at the inflection point at 30 s.